Globalization and cultural standards in Emirati society: A study on a sample of students at the University of Sharjah - Al Nuaimi, Majed; Al-Taii, Alaa (Al-Adab Journal, 2025)
The study aimed to investigate the expected effects of globalization on cultural standards in the United Arab Emirates society, based on the opinions of a purposive sample of students from the University of Sharjah, totaling 300 students. The study employed a descriptive-analytical approach, utilizing social survey method to reach the targeted observation units. Eleven research variables were used, along with several statistical methods to present the results. The study results revealed that concerning the main variable of the study and its three primary axes and sub-items related to the awareness of the sample individuals about the effects of globalization on cultural standards in the United Arab Emirates, there was an increase in awareness levels among most of the study sample. The analytical results of the study indicated differences between citizens and expatriates regarding awareness of the manifestations and effects or changes brought about by the spread of globalization in Emirati society. Unexpectedly, these results favored the expatriates. This is attributed to the fact that the United Arab Emirates, through its respect and promotion of values of tolerance and coexistence, has created a unique sense of belonging among expatriates. This has reinforced the sense of belonging and loyalty among both citizens and residents to the extent that residents have become aware of the impact of globalization on the local culture. The study recommended the continued enhancement of the state's practices of coexistence and tolerance as a preventive measure against the negative impact on the nation's partners. The study also provided several suggestions to support the positive effects of globalization and mitigate its negative effects on cultural standards.